A new genus of fruit fly in subfamily Dacinae (Diptera: Tephritidae) from India - David, K.j.; Hancock, D.l.; Gracy, R.g.; Sachin, K. (Zootaxa, 2022)
A new genus and species of fruit fly, Dacimita curvifasciatus David & Hancock, gen. et sp. n. is described from Meghalaya, India. It morphologically resembles Ichneumonopsis Hardy and Monacrostichus Bezzi, the former of uncertain tribal placement and the latter included in tribe Dacini. Phylogenetic analysis based on morphological and molecular characters revealed Dacimita curvifasciatus to be best placed in tribe Gastrozonini in subfamily Dacinae.